RETRACTED: Investigating the Effects of Advanced Heat Treatment Techniques on the Mechanical Properties of Cast Components - Singh Bharat; Anupama B.; Kalra Ravi; Dhamija Koushal; Kareem Ali; Kumar Manish (E3S Web of Conferences)
The Publisher has been made aware of ethical breaches affecting this proceeding published in E3S Web of Conferences, Volume 430 (2023). These instances involve a specific author, K.K. Saxena who used citation manipulation and inappropriate references in 47 articles, for a total of 310 citations. We are extremely concerned by such malpractice which considerably impacts the image of our title and our Publisher’s reputation. See our publishing ethics policies. The Guest Editor of the proceedings volume endorsed the Publisher's decision to retract these articles. Web of Conferences is extremely grateful to the whistleblower for bringing this case to our attention. See the retraction notice E3S Web of Conferences 430, 00002 (2023), https://doi.org/10.1051/e3sconf/202443000002